2016
DOI: 10.1038/srep31880
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Choroidal Neovascularization: Intraocular Inflammatory Cytokines and the Effect of Intravitreal Ranibizumab Treatment

Abstract: Idiopathic choroidal neovascularization (ICNV) is a disorder that primarily affecting patients younger than 50 years and can cause severe loss of vision. Choroidal abnormalities, especially choroidal inflammation, have been thought to be involved in the pathophysiology of ICNV. However, the exact pathogenesis of ICNV remains unclear. The aim of our study was investigate the levels of 27 inflammatory cytokines in the aqueous humor of eyes with ICNV, and to determine the effect of intravitreal injection of ranib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 48 publications
(61 reference statements)
0
17
1
1
Order By: Relevance
“…In eyes with choroidal neovascularization, elevated IL-17 was detected in aqueous humor when compared with the control group, leading to the hypothesis that this cytokine may stimulate angiogenesis in a VEGF-independent manner [ 103 ]. IL-10 is another interleukin that can promote pathological neovascularization [ 104 ].…”
Section: Resultsmentioning
confidence: 99%
“…In eyes with choroidal neovascularization, elevated IL-17 was detected in aqueous humor when compared with the control group, leading to the hypothesis that this cytokine may stimulate angiogenesis in a VEGF-independent manner [ 103 ]. IL-10 is another interleukin that can promote pathological neovascularization [ 104 ].…”
Section: Resultsmentioning
confidence: 99%
“…This was consistent with the study by Sudhalkar A et al [16] which showed that patients with a higher baseline BCVA had a better prognosis. These findings might relate to the high permeability of neovascular structures, which could cause bleeding and exudation and induce inflammatory reactions and retinal damage [5,22]. ICNV patients with a good baseline BCVA might not suffer from irreversible inflammatory effects and retinal damage; therefore, our results suggest that timely anti-VEGF treatment can effectively reduce the inflammatory response and make CNV lesions subside, in turn leading to a better prognosis.…”
Section: Discussionmentioning
confidence: 77%
“…It has been suggested that when abnormal blood vessels originating from the choriocapillaris break through the Bruch membrane and grow in the retinal pigment epithelium (RPE) or infiltrates into the subretinal pigment epithelium or subretinal space [2,3], they can result in CNV. CNV that develops in younger patients who are less than 50 years old is usually attributed to pathologic myopia, angioid streaks, trauma, cytomycosis, central serous chorioretinopathy (CSC) and other hereditary ocular diseases [4,5]. However, the cause of CNV still remains unclear in a large number of younger patients.…”
Section: (Continued From Previous Page)mentioning
confidence: 99%
“…This was consistent with the study by Sudhalkar A et al (16) which showed that patients with a higher baseline BCVA had a better prognosis. These findings might relate to the high permeability of neovascular structures, which could cause bleeding and exudation and induce inflammatory reactions and retinal damage (5,22). ICNV patients with a good baseline BCVA might not suffer from irreversible inflammatory effects and retinal damage; therefore, our results suggest that timely anti-VEGF treatment can effectively reduce the inflammatory response and make CNV lesions subside, in turn leading to a better prognosis.…”
Section: Comparison Between Subgroups According To Baseline Bcvamentioning
confidence: 77%
“…CNV that develops in younger patients who are less than 50 years old is usually attributed to pathologic myopia, angioid streaks, trauma, cytomycosis, central serous chorioretinopathy (CSC) and other hereditary ocular diseases (4,5). However, the cause of CNV still remains unclear in a large number of younger patients.…”
Section: Introductionmentioning
confidence: 99%